Contribution of MEK Inhibition to BRAF/MEK Inhibitor Combination Treatment of BRAF-Mutant Melanoma: Part 2 of the Randomized, Open-Label, Phase III COLUMBUS Trial - Ascierto, Paolo A; Dummer, Reinhard; Gogas, Helen J; Arance, Ana; Mandala, Mario; Liszkay, Gabriella; Garbe, Claus; Schadendorf, Dirk; Krajsova, Ivana; Gutzmer, Ralf; Chiarion-Sileni, Vanna; Dutriaux, Caroline; et al. (Journal of clinical oncology, 2023)
PURPOSE: In COLUMBUS part 1, patients with advanced BRAFV600-mutant melanoma were randomly assigned 1:1:1 to encorafenib 450 mg once daily plus binimetinib 45 mg twice a day (COMBO450), vemurafenib 960 mg twice a day, or encorafenib 300 mg once daily (ENCO300). As previously reported, COMBO450 improved progression-free survival (PFS) versus vemurafenib (part 1 primary end point) and ENCO300 (part 1 key secondary end point; not statistically significant). Part 2, requested by the US Food and Drug Administration, evaluated the contribution of binimetinib by maintaining the same encorafenib dosage in the combination (encorafenib 300 mg once daily plus binimetinib 45 mg twice daily [COMBO300]) and ENCO300 arms. METHODS: In part 2, patients were randomly assigned 3:1 to COMBO300 or ENCO300. ENCO300 (parts 1 and 2) data were combined, per protocol, for PFS analysis (key secondary end point) by a blinded independent review committee (BIRC). Other analyses included overall response rate (ORR), overall survival, and safety. RESULTS: Two hundred fifty-eight patients received COMBO300, and 86 received ENCO300. Per protocol, ENCO300 arms (parts 1 and 2 combined) were also evaluated (n = 280). The median follow-up for ENCO300 was 40.8 months (part 1) and 57.1 months (part 2). The median PFS (95% CI) was 12.9 months (10.9 to 14.9) for COMBO300 versus 9.2 months (7.4 to 11.1) for ENCO300 (parts 1 and 2) and 7.4 months (5.6 to 9.2) for ENCO300 (part 2). The hazard ratio (95% CI) for COMBO300 was 0.74 (0.60 to 0.92; two-sided P = .003) versus ENCO300 (parts 1 and 2). The ORR by BIRC (95% CI) was 68% (62 to 74) and 51% (45 to 57) for COMBO300 and ENCO300 (parts 1 and 2), respectively. COMBO300 had greater relative dose intensity and fewer grade 3/4 adverse events than ENCO300. CONCLUSION: COMBO300 improved PFS, ORR, and tolerability compared with ENCO300, confirming the contribution of binimetinib to efficacy and safety.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Melanoma; Vemurafenib; inhibitory proteinkinas; protokoly protinádorové kombinované chemoterapie; mitogenem aktivované proteinkinasy kinas; mutace; melanom; protoonkogenní proteiny B-raf; Humans; Mutation; Protein Kinase Inhibitors; nádory kůže; Mitogen-Activated Protein Kinase Kinases; Proto-Oncogene Proteins B-raf; Skin Neoplasms; lidé; vemurafenib